Gambaran Kebahagiaan Lanjut Usia yang Tinggal di Panti Tresna Werdha Sabai Nan Aluih Sicincin - Sucitra Indriani; Afrinaldi Afrinaldi; Zulfani Sesmiarni; Dodi Pasila Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study focuses on the happiness of the elderly living in Panti Tresna Werdha Sabai Nan Aluih Sicincin, Padang Pariaman. An important part to help the elderly overcome the problems they face. This study aims to describe how happy the elderly are in the shelter, where happy elderly tend to be more open to new activities and have lower mortality and death rates. The method used is descriptive qualitative, with the main informant being the shelter officer and the elderly as supporting informants, and the study was conducted from January to June 2022. The results of the study show that the happiness of the elderly is reflected in their daily activities, such as skills guidance, health, religion, arts, social, to mutual cooperation and gymnastics. The elderly also fill their free time by reading the Qur'an and cleaning the environment. They feel happy because they are treated well, do not feel lonely, and consider the residents and staff of the shelter as family. Most of the elderly are comfortable living in the shelter and do not want to go home, even want to be buried there, showing that their happiness has been fulfilled at Panti Tresna Werdha Sabai Nan Aluih Sicincin.